Persistency, medication prescribing patterns, and medical resource use associated with multiple sclerosis patients receiving oral disease-modifying therapies: a retrospective medical record review. Issue 1 (December 2016) - Nazareth, Tara; Friedman, Howard; Navaratnam, Prakash; Herriott, Denise; Ko, John; Barr, Peri; Sasane, Rahul
Abstract Background In the US, the approved multiple sclerosis (MS) oral disease-modifying therapies (ODMTs) are fingolimod (FTY), teriflunomide (TFN), and dimethyl fumarate (DMF). FTY and TFN are recommended with once-daily doses with no up-titration, whereas DMF treatment is recommended twice-daily (BID) and is initiated with a 7-day starter dose of 120 mg BID before up-titration to the maintenance dose of 240 mg BID. Limited information exists regarding real-world ODMT prescribing patterns to aid physician/patient decision-making. Methods Eligible patients for this retrospective medical record review were ≥18 years, had one visit related to ODMT initiation (index visit), and ≥1 visit within 12 months before and after the index visit. Primary objectives were to assess post-index ODMT persistency (i.e., discontinuation), prescribing patterns (medication switching, dose up-titrations, dose reduction, re-starts, and add-ons) and medical resource utilization (office-visits, MRI procedures, and mobility indicators) at distinct time windows of 3, 6, 9, and 12 months. Chi-square or Wilcoxon Rank Sum tests were used for 3-way ODMT group comparisons. Results Medical records of 293 MS-diagnosed patients using ODMTs were abstracted from 19 US-based neurology clinics between December 31, 2010 and June 30, 2014 (FTY: 101; DMF: 133; TFN: 59). Persistency rates among ODMT groups were similar. MS-related medication switching, dose reduction, re-starts, and add-ons were infrequently observed and were similar across ODMT groups. Of DMF patients with a confirmed starting dose of 120 mg BID with ≥12 months follow-up (n = 26), the percentage who were prescribed dose up-titrations to the recommended maintenance DMF dose was 23.1 % at 1–3 months, 26.9 % at 4–6 months, 42.3 % at 7–9 months, and 0 % at 10–12 months. There were no significant differences at any time window among the ODMT groups in the number of office visits or percent of patients receiving MRIs. Mobility indicator patterns (proportion of patients with abnormal gait, wheelchair use, etc.) were consistent over time. Conclusions There was no difference in persistency, prescribing patterns (medication switching, dose reduction, re-starts, and add-ons) or medical resource utilization (office-visits, MRI procedures, and mobility indicators) among the ODMTs. However, in a small sub-group of patients, delays of up to 9 months in DMF dose-up titration to the recommended maintenance dose were observed.